Internal Migration of Workers in the European Union: Legal Aspects of Lithuania’s Experience in Transposing the Posting of Workers Directive - Krasauskas Rytis; Mačernytė-Panomariovienė Ingrida (Baltic Journal of Law & Politics, 2021)
Freedom to provide services and free movement of workers are linked to the processes of permanent intra-EU migration, which are regulated, inter alia, by the national legislation implementing PWD. Consequently, the posting of workers within EU is not only part of the work organization process, but also part of a wider phenomenon of internal migration of workers. Accordingly, posted workers are to be considered as internal labour migrants. The regulation of the posting of workers must consider the legitimate interest of Member States in protecting their markets from social dumping as well as ensure minimum guarantees for posted workers. These circumstances presuppose changes in the regulation of the posting of workers. This article identifies four stages in the transposition of PWD into Lithuanian national law that are causally related to changes in European legislation and Lithuanian labour law reform as of 2017. It presents the legal assessment of national legal regulation and case law, identifying the related legal problems. The article pays special attention to the legal regulation of the remuneration of a posted worker, established by PWD (Directive 96/71/EC of the European Parliament and of the Council on 16 December 1996 concerning the posting of workers in the framework of the provision of services (Official Journal (EU), 2004, no. L 18) [Directive 96/71/EC], with the amendments introduced by Directive 2014/67/EU of the European Parliament and of the Council from 15 May 2014 on the enforcement of Directive 96/71/EC concerning the posting of workers in the framework of the provision of services and amending Revision 4 of the EU Posting of Workers Directive Regulation (EU) No 1024/2012 on administrative cooperation through the Internal Market Information System (‘the IMI Regulation’) (Official Journal (EU), 2014, no. L 159) [Directive 2014/67/EU] and Directive 2018/957/EU of the European Parliament and of the Council on June 2018 amending Directive 96/71/EC concerning the posting of workers in the framework of the provision of services (Official Journal (EU), 2018, no. L 173) [Directive 2018/957/EU]). It also explains the impact on the regulation of employment relations for posted workers in Lithuania stemming from Directive 2019/1152 on transparent and predictable working conditions in the EU.